2021
DOI: 10.2147/tcrm.s321410
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Results Between “Epi-Off” Accelerated and “Epi-Off” Standard Corneal Collagen Crosslinking-UVA in Progressive Keratoconus – 7 Years of Follow-Up

Abstract: The purpose of the present study was to assess the long-term efficiency and safety of the "epi-off" accelerated CXL (9 mW/cm 2 for 10 minutes) in comparison to the standard "epi-off" CXL (3 mW/cm 2 for 30 minutes) in terms of topographical and keratometric parameters, refractive data and visual outcomes at 7 years of follow-up, in progressive keratoconus. Material and Method: A retrospective and comparative study was performed. A total of 183 eyes from 183 patients with documented progressive keratoconus were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Of the 9/18 (50%) of studies reviewed with reported progression criteria, follow-up ranged from 3 to 13 years and post-CXL progression rates ranged between 0.8 and 33% [26,31,40,44 One study had one participant with a persistent epithelial defect [31]. Microbial keratitis was found in 2.6% of patients in one manuscript [40], while persistent corneal haze or scarring was found in & ] while in the 18 that examined best corrected visual acuity (BCVA) or corrected distance visual acuity (CDVA), eight of 18 (44.4%) identified no significant change [23,25,39,40,42,45,49 ,50] and 10 of 18 (55.6%) documented statistically significant improvements at 2-10 years…”
Section: Standard Dresden Protocolmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 9/18 (50%) of studies reviewed with reported progression criteria, follow-up ranged from 3 to 13 years and post-CXL progression rates ranged between 0.8 and 33% [26,31,40,44 One study had one participant with a persistent epithelial defect [31]. Microbial keratitis was found in 2.6% of patients in one manuscript [40], while persistent corneal haze or scarring was found in & ] while in the 18 that examined best corrected visual acuity (BCVA) or corrected distance visual acuity (CDVA), eight of 18 (44.4%) identified no significant change [23,25,39,40,42,45,49 ,50] and 10 of 18 (55.6%) documented statistically significant improvements at 2-10 years…”
Section: Standard Dresden Protocolmentioning
confidence: 99%
“…Long-term data on CXL for progressive pediatric KCN suggest that overall SDP and newer techniques do not successfully halt progression as effectively as in adults, while visual and topographic outcomes vary significantly between studies. postprocedure [22,26,31,33,41,43,44…”
Section: Key Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly used method in clinical practice is the standard Dresden protocol for corneal crosslinking (S-CXL). However, S-CXL is time-consuming, and although prior studies report comparable efficacies of accelerated CXL (A-CXL) and S-CXL [ 4 , 5 ], some clinical centers do not currently use conventional S-CXL to treat keratoconus. Moreover, removal of the corneal epithelium may cause pain, discomfort, temporary vision reduction, and decreased corneal clarity (haze), and can increase the risk of infectious keratitis [ 6 – 8 ].…”
Section: Introductionmentioning
confidence: 99%